Aset dan Strategi Penghidupan Petani Karet di Area Transmigrasi Lampung: Aset dan Strategi Penghidupan Petani Karet di Area Transmigrasi Lampung - Ayu Ningtiyas, Luluk; Izzudin, Muhammad (Jurnal Sosial Ekonomi Pertanian, 2025)
This study aims to examine the relationship between livelihood assets and the livelihood strategies of rubber farmers in Bumi Baru Village, Way Kanan Regency, Lampung Province—a transmigration area where the majority of the population relies on rubber cultivation for their livelihood. This study used a quantitative correlational approach with 68 respondents selected through a simple random sampling method. Five types of livelihood capital were analyzed: human, social, financial, physical, and natural capital. Livelihood strategies were categorized as intensification, extensification, diversification, and migration. The analysis showed that human capital had the highest score (94.6%), while social capital was the weakest (75.8%). The most dominant livelihood strategy was intensification, specifically the use of plant vitamins and garden maintenance. A Pearson correlation test revealed a positive and significant relationship between livelihood assets and rubber farmers' livelihood strategies (r = 0.477; p = 0.000), indicating that the stronger the assets held by farmers, the greater their adaptive capacity to economic and ecological pressures. These findings reinforce the importance of a development approach based on strengthening livelihood assets as a foundation for sustainable survival strategies. Policy recommendations include farmer training, access to microcredit, strengthening farmer institutions, and productive land management. The analysis showed that human capital had the highest score (94.6%), while social capital was the weakest (75.8%). The most dominant livelihood strategy was intensification, specifically the use of plant vitamins and garden maintenance. A Pearson correlation test revealed a positive and significant relationship between livelihood assets and rubber farmers' livelihood strategies (r = 0.477; p = 0.000), indicating that the stronger the assets held by farmers, the greater their adaptive capacity to economic and ecological pressures. These findings reinforce the importance of a development approach based on strengthening livelihood assets as a foundation for sustainable survival strategies. Policy recommendations include farmer training, access to microcredit, strengthening farmer institutions, and productive land management.